Functional heterogeneity and high frequencies of cytomegalovirus-specific CD8(+) T lymphocytes in healthy seropositive donors. - Gillespie, G; Wills, MR; Appay, V; O'Callaghan, C; Murphy, M; Smith, N; Sissons, P; Rowland-Jones, S; Bell, J; Moss, P (2000)
Human cytomegalovirus (HCMV) infection is largely asymptomatic in the immunocompetent host, but remains a major cause of morbidity in immunosuppressed individuals. Using the recently described technique of staining antigen-specific CD8(+) T cells with peptide-HLA tetrameric complexes, we have demonstrated high levels of antigen-specific cells specific for HCMV peptides and show that this may exceed 4% of CD8(+) T cells in immunocompetent donors. Moreover, by staining with tetramers in combination with antibodies to cell surface markers and intracellular cytokines, we demonstrate functional heterogeneity of HCMV-specific populations. A substantial proportion of these are effector cytotoxic T lymphocytes, as demonstrated by their ability to lyse peptide-pulsed targets in "fresh" killing assays. These data suggest that the immune response to HCMV is periodically boosted by a low level of HCMV replication and that sustained immunological surveillance contributes to the maintenance of host-pathogen homeostasis. These observations should improve our understanding of the immunobiology of persistent viral infection.